INOVASI PEMBELAJARAN COLLABORATIVE LEARNING TIPE SMALL GROUP DISCUSSION DALAM MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA DI MA MA’ARIF SUKOREJO: pembelajaran Collaborative Learning, tipe small group discussion, penerapan, dampak - dewi; Muhammad Nur Hadi (IAIN Ambon, 2025)
The purpose of this study is to be able to develop collaborative learning innovations of the Small Group Discussion type to improve communication skills among students at MA Ma'arif Sukorejo. This study uses a qualitative case study research type using data collection techniques in the form of observation, interviews, documentation. The results of this study are that at MA Ma'arif Sukorejo schools often experience challenges related to the lack of communication skills among students. This is usually a way for a teacher to convey material by talking more and students only listening. So that the collaborative learning model of the Small Group Discussion type can help students in the learning process to be more efficient and not monotonous, cooperation carried out by students can bind the bonds of unity, responsibility, students can exchange information and experiences in solving problems, students can gain more knowledge and experience from the activities they do.